DINAMIKA TERORISME DI INDONESIA STUDI TENTANG LOKALISASI IDEOLOGI EKSTERNAL - Vanny El Rahman (UIN Syarif Hidayatullah Jakarta, 2020)
AbstrakThe terrorism movement in Indonesia has developed from time to time. It perceived when comparing the perceptions of The Indonesian Islamic State from each group. Darul Islam, the root of the extremism movement, echoed the narrative of jihad against the colonialist. They believed that theocracy was an ideal state construction amidst the disappointing policies of the Central Government at the beginning of independence. In the meantime, the perception of Jemaah Islamiyah towards an Islamic state was full of Salafi nuances because they believed that its establishment as an obligation for every Muslim. Meanwhile, Jemaah Ansharul Daulah noticed The Indonesian Islamic State as only part of a global caliphate. The author argues that this dynamic is caused by the phenomenon of ideological internalisation. By combining localization theory and ideological concepts, this article concluded that the ideological localization of external radicalism occurred for three reasons, namely moral compliance to adopt a more argumentative ideology, rational calculations of strategies that can be implemented in the local context and temporary strategies to maintain group existence.